Volcanic eruption eye-witnessed and recorded by prehistoric humans - Ulusoy, Inan; Sarikaya, M. Akif; Schmitt, Axel Karl (Quaternary science reviews, 2019)
Human footprints in hydrovolcanic ash near Çakallar volcano (Kula, Western Turkey) were discovered in 1968. A nearby pictograph interpreted as depicting Çakallar volcano would define it as the oldest site where humans demonstrably eye-witnessed a volca̶nic eruption and possibly artistically recorded it. Despite Çakallar's volcanological and cultural importance, its eruption age has remained controversial. Here, two independent dating methods, cosmogenic 36Cl and combined U-Pb and (U-Th)/He zircon (ZDD) geochronology, yielded the first internally consistent eruption ages controlled by detailed volcanostratigraphic mapping. Concordant 36Cl ages of 4.7±0.6 ka (errors 1σ) were obtained for a cone-breaching lava flow. ZDD ages for crustal xenoliths from scoria deposits directly overlying the footprints yielded an age of 4.7±0.7 ka. This firmly places the Çakallar eruption and prehistoric human footprints, and plausibly the rock art, into the Bronze Age, reinforcing the notion that prehistoric artwork recorded natural events.